2013
DOI: 10.3389/fendo.2013.00105
|View full text |Cite
|
Sign up to set email alerts
|

RAGE-Mediated Inflammation, Type 2 Diabetes, and Diabetic Vascular Complication

Abstract: Obesity is associated with inflammation and type 2 diabetes. Innate immune system comprised of cellular and molecular components plays an important role in the inflammatory reactions. Immune cells like macrophages and their cell surface pattern-recognition receptors (PRRs) are representative for innate immunity promoting inflammatory reactions. The receptor for advanced glycation end-products (RAGE) is a member of PRRs and a proinflammatory molecular device that mediates danger signals to the body. The express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 24 publications
1
57
0
8
Order By: Relevance
“…Corvera et al (38) proposed that during diabetic complications, the early formation of advanced glycation end products associated with hyperglycemia stimulates mechanisms that lead to the recruitment of key components of the inflammatory response. Indeed, studies have shown that the advanced glycation end products receptor-mediated regulation of adiposity and inflammation may result in T2D and diabetic vascular complications (39). Other research has shown that serum levels of IL6, IL17, interferon g, TNFg, IL2, and IL10 were increased in T2D nephropathy (T2DN) Adjusted hazard ratios (HRs) (95% CI) of the relationship between the quintiles (Q) of leukocyte, neutrophil, and lymphocyte counts and the incidence of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Corvera et al (38) proposed that during diabetic complications, the early formation of advanced glycation end products associated with hyperglycemia stimulates mechanisms that lead to the recruitment of key components of the inflammatory response. Indeed, studies have shown that the advanced glycation end products receptor-mediated regulation of adiposity and inflammation may result in T2D and diabetic vascular complications (39). Other research has shown that serum levels of IL6, IL17, interferon g, TNFg, IL2, and IL10 were increased in T2D nephropathy (T2DN) Adjusted hazard ratios (HRs) (95% CI) of the relationship between the quintiles (Q) of leukocyte, neutrophil, and lymphocyte counts and the incidence of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…RAGE-mediated regulation of adiposity and inflammation may attribute to type 2 diabetes and diabetic vascular complications. 6 RAGE provides a new target for the treatment interventions to reduce and prevent the development of side effects of hyperglycemia. It is possible to make personalized therapy against RAGE to inhibit disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Adipose tissue consists of heterogeneous populations of adipocytes, stromal preadipocytes, immune cells, and vascular cells, and it can respond rapidly and dynamically to alterations in nutrient excess caused by enhanced food consumption through adipocyte hypertrophy and hyperplasia (Shoelson et al, 2006). This results in a local infl ammation in adipose tissue that propagates an overall systemic but chronic low-grade infl ammation associated with the development of obesity-related comorbidities such as type 2 diabetes and cardiovascular diseases (Yamamoto and Yamamoto, 2013). The possibility that obesity, and the activation of adipose tissue in particular, may enhance the release of infl ammatory factors that underlie the development of insulin resistance has generated intense interest in the fi eld of diabetes for a number of reasons.…”
mentioning
confidence: 99%